Bridging the critical interface: Ambidextrous innovation for water provision in Nairobi's informal settlements. (February 2020) - Blomkvist, Pär; Nilsson, David; Juma, Benard; Sitoki, Lewis
Abstract: This article examines innovation activities in water infrastructure in Nairobi, Kenya. The focus is on efforts by Nairobi City Water and Sewerage Corporation (NCWSC) to provide water services to the inhabitants in the informal areas of the city using an automated vending machine, or Pre-Paid Dispenser (PPD). In this study, we investigate what happens when a regime actor like NCWSC tries to implement an ambidextrous (two-handed) strategy: managing the existing system according to conventional practice and at the same time innovate in new technical solutions and business models to cater for unconnected users. Besides presenting our results, our aim in this article is also to introduce a research strategy for innovation studies in infrastructural systems in low-income urban areas. Three interconnected parts stand out as our contribution: First, we present a novel conceptual framework, by adding ideas from innovation studies to the Large Technical Systems approach. We investigate how regime actors can innovate to provide water to unconnected users, without expanding the system in a traditional way. Second, we propose a novel method for analysing and understanding innovation on the margins of the infrastructural system, or in our terms, innovation in the critical interface . Central to our method is, through empirical observation, to identify misalignment between the innovation (PPD) and contextual factors at the local level, where the innovation is implemented (interface misalignment), and misalignment between the innovation and the existing water regime (internal misalignment). We use a qualitative method and results forms as a basis for further research and starting point for regime actors in search of an improved ambidextrous strategy. Third, we analyse the innovation process per se. In the Nairobi case, we assess the ambidextrous innovation strategy, and claim that the PPD functions as an adapter in the critical interface, enabling the regime actors to operate in an environment of misalignment. Highlights: Novel theoretical framework combines Large Technical Systems with Innovation Theory applied to water provision in Kenya. Pre-paid technology hampered by misalignment in socio-political and technical areas as well as business models. Using an ambidextrous organisational approach requires new skills set and routines. The pre-paid water dispenser is an adaptive innovation for low-income customers while preserving core business.